Root-secreted nucleosides: signaling chemoattractants of rhizosphere bacteria - Keren, Guy; Yehezkel, Galit; Satish, Lakkakula; Adamov, Zahar; Barak, Ze’ev; Ben-Shabat, Shimon; Kagan-Zur, Varda; Sitrit, Yaron (Frontiers in Plant Science, 2024)
The rhizosphere is a complex ecosystem, consisting of a narrow soil zone influenced by plant roots and inhabited by soil-borne microorganisms.Plants actively shape the rhizosphere microbiome through root-exudates. Some metabolites are signaling molecules specifically functioning as chemoattractants rather than nutrients. These elusive signaling molecules have been sought for several decades, and yet little progress has been made.Root-secreted nucleosides and deoxy nucleosides were detected in exudates of various plants by targeted UPLC-MS/MS. Rhizobacteria were isolated from the roots of Helianthemum sessiliflorum carrying the mycorrhizal desert truffle Terfezia boudieri. Chemotaxis was determined by a glass capillary assay or plate assays on semisolid agar and through soil plate assay.Nucleosides were identified in root exudates of plants that inhabit diverse ecological niches. Nucleosides induced positive chemotaxis in plant beneficial bacteria Bacillus pumilus, Bacillus subtilis, Pseudomonas turukhanskensis spp., Serratia marcescens and the pathogenic rhizobacterium Xanthomonas campestris and E coli. In a soil-plate assay nucleosides diffused to substantial distances and evoked chemotaxis under conditions as close as possible to natural environments.This study implies that root-secreted nucleosides are involved in the assembly of the rhizosphere bacterial community by inducing chemotaxis towards plant roots. In animals, nucleosides secretion known as "purinergic signaling" is involved in communication between cells, physiological processes, diseases, phagocytic cells migration, and bacterial activity. The coliform bacterium E. coli which inhabits the lower intestine of warmblooded organisms also attracted to nucleosides implying that nucleosides may serve as a common signal for bacteria species inhabiting distinct habitats. Taken together all these may indicate that chemotaxis signaling by nucleosides is a conserved universal mechanism that encompasses living kingdoms and environments and should be given further attention in plant rhizosphere microbiome research.